Method for preparing edge-selectively etched palladium metal films and applications thereof
Patent Information
- Application Number
- CN202311144908.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-09-06
AI Technical Summary
Existing technologies struggle to maintain the surface structure of palladium metal olefins while increasing the proportion of edge sites, resulting in insufficient electrochemically active specific surface area and catalytic activity, particularly poor performance in formic acid oxidation reactions.
By employing an edge-selective etching method, palladium metal olefins are generated by introducing carbon monoxide gas after dissolving a palladium precursor, followed by heating in an acetic acid solution. The etching conditions are controlled to maintain the planar structure of the palladium metal olefins and enhance edge etching, thus preparing a palladium metal olefin catalyst with a high electrochemically active specific surface area.
The prepared edge-selective etched palladium metal olefin catalyst significantly improves the electrochemically active specific surface area and formic acid oxidation catalytic activity while maintaining the surface structure, making it suitable for applications such as direct formic acid fuel cells, biosensing, and metal-air batteries.
Smart Images

Figure CN117174928B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to the preparation method and application of edge-selective etching of palladium metal olefins. Background Technology
[0002] Metalloalenes are a class of metastable two-dimensional metallic materials with atomic-level thickness and graphene-like structures. Due to their ultra-high surface area and the resulting large number of unsaturated metal atoms, they have attracted widespread attention from researchers in the field of energy catalysis. In 2019, Guo Shaojun et al. from Peking University published a research paper in Nature entitled "PdMo bimetallene for oxygen reduction catalysis," reporting PdMo bimetallene for the first time. Guo et al. used a highly coordinated metal precursor as a reactant and obtained highly coiled two-dimensional PdMo bimetallene through a low-temperature, long-term liquid-phase reaction under a weakly reducing environment, achieving an important application in metal-air batteries (Nature, 2019, DOI: 10.1038 / s41586-019-1603-7). Optimization of the surface structure of palladium metalloalenes will further expand their application range.
[0003] Electrocatalytic reactions are interfacial reactions, therefore the surface physicochemical properties of catalysts are crucial for optimizing catalytic performance. Increasing the electrochemically active specific surface area of a catalyst helps promote reactant adsorption and exposes more active sites, thus facilitating efficient catalytic reactions and improving electrode process kinetics. For palladium metallobens, most current strategies for increasing their electrochemically active specific surface area involve etching porous structures on their surface using methods such as plasma etching. However, this indiscriminate etching easily leads to the collapse and accumulation of the overall palladium metalloben structure. Furthermore, studies have shown that edge sites in palladium metallobens have a higher proportion of unsaturated sites, resulting in higher catalytic activity in many cases compared to planar sites. Maintaining the surface structure of palladium metallobens and increasing the proportion of edge sites is an important strategy for improving their electrochemically active specific surface area, exposing more catalytic active sites, and ultimately enhancing electrocatalytic performance. However, research on maintaining the surface structure of palladium metallobens while increasing the proportion of edge sites has not yet been reported. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing edge-selectively etched palladium metal olefins. The prepared palladium metal olefin catalyst has a high electrochemically active specific surface area and formic acid oxidation catalytic activity. Moreover, the method is simple, highly reproducible, and suitable for large-scale preparation. The present invention also provides the electrocatalytic application of the edge-selectively etched palladium metal olefins.
[0005] This invention is achieved through the following technical solution:
[0006] The method for preparing edge-selectively etched palladium metal olefins according to the present invention includes the following steps:
[0007] (1) Dissolve the palladium precursor in methanol, pass carbon monoxide gas through it, react to generate palladium metal olefin, centrifuge and wash to obtain palladium metal olefin.
[0008] (2) Disperse palladium metal olefin in acetic acid solution;
[0009] (3) After sealing and heating the mixed solution obtained in step (2), keep it at a constant temperature;
[0010] (4) The product obtained in step (3) is centrifuged, washed and dried to obtain the edge-selectively etched palladium metal olefin.
[0011] In step (1), the palladium precursor includes ammonium chloropalladium, sodium chloropalladium or potassium chloropalladium. The mass-volume ratio of palladium to methanol in the palladium precursor is 0.05 to 50:1 (mg / mL). The palladium precursor has high solubility in methanol. It is preferred to use ultrasonic mixing at a temperature of 20 to 80°C. Appropriately increasing the temperature can further improve the dissolution efficiency. At the same time, ultrasonic mixing can avoid the introduction of impurities and their impact on the reaction.
[0012] After carbon monoxide gas is introduced, palladium metal olefin can be rapidly generated. The preferred time for introducing carbon monoxide gas is 5 to 30 minutes.
[0013] In step (2), the concentration of the acetic acid solution is 0.1 to 1.0 mol / L, and the mass-to-volume ratio of palladium metal olefin to acetic acid solution is 0.1 to 50:1 (mg / mL).
[0014] In step (3), the mixed solution is heated to a certain temperature and then kept at that temperature for a certain period of time. The heating temperature is 80℃~110℃ and the holding time is 2.0h~10h.
[0015] In step (4), the drying temperature is 40℃~100℃ and the time is 10~20h.
[0016] The washing solution used is ethanol or water, and it can be washed several times. It should be noted that the last washing solution should be water.
[0017] The edge-selective etched palladium metal olefin described in this invention can be directly used as an anode catalyst for formic acid fuel cells, and can also be used as a catalyst in energy storage / conversion fields such as biosensing, industrial catalysis, and metal-air batteries.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The method described in this invention can achieve edge-selective etching of palladium metal olefins while maintaining their surface structure. Compared with unetched palladium metal olefins, the edge-selectively etched palladium metal olefins prepared have a larger electrochemically active specific surface area and higher formic acid oxidation catalytic activity, which has high practical value as an anode catalyst for direct formic acid fuel cells and in other energy storage / conversion fields. Furthermore, the method of this invention is simple to operate, highly reproducible, and can be extended to prepare other edge-selectively etched nanostructure two-dimensional materials with a wide range of applications and prospects. Attached Figure Description
[0020] Figure 1 Transmission electron microscopy image of the edge-selective etching palladium metal olefin catalyst prepared in Example 1;
[0021] Figure 2 This is a comparison of cyclic voltammetry curves in 0.5 M H2SO4 solution between the edge-selectively etched palladium metal olefin catalyst prepared in Example 1, the unetched palladium metal olefin, and the commercial palladium / carbon catalyst.
[0022] Figure 3 A comparison of the catalytic activities of the edge-selectively etched palladium metal olefin catalyst prepared in Example 1, the unetched palladium metal olefin catalyst, and the commercial palladium / carbon catalyst in 0.5 M H2SO4 + 0.5 M HCOOH solution;
[0023] Figure 4 Transmission electron microscopy image of the edge-selective etching palladium metal olefin catalyst prepared in Example 2;
[0024] Figure 5 A comparison of cyclic voltammetry curves in 0.5 M H2SO4 solution between the edge-selectively etched palladium metal olefin catalyst prepared in Example 2, the unetched palladium metal olefin, and the commercial palladium / carbon catalyst.
[0025] Figure 6 This is a comparison of the catalytic activities of the edge-selectively etched palladium metal olefin catalyst prepared in Example 2, the unetched palladium metal olefin catalyst, and the commercial palladium / carbon catalyst in 0.5 M H2SO4 + 0.5 M HCOOH solution.
[0026] Figure 7 Transmission electron microscopy image of the edge-selective etching palladium metal olefin-1 catalyst prepared in Comparative Example 1;
[0027] Figure 8 Comparison of cyclic voltammetry curves in 0.5 M H2SO4 solution between the edge-selectively etched palladium metal olefin-1 catalyst prepared in Comparative Example 1, the unetched palladium metal olefin, and the commercial palladium / carbon catalyst;
[0028] Figure 9Comparison of the catalytic activities of the edge-selectively etched palladium metal olefin-1 catalyst prepared in Comparative Example 1, the unetched palladium metal olefin, and the commercial palladium / carbon catalyst in 0.5 M H2SO4 + 0.5 M HCOOH solution;
[0029] Figure 10 Transmission electron microscopy image of the edge-selective etching palladium metal olefin-2 catalyst prepared in Comparative Example 2;
[0030] Figure 11 Comparison of cyclic voltammetry curves in 0.5 M H2SO4 solution between the edge-selectively etched palladium metal olefin-2 catalyst prepared in Comparative Example 2, the unetched palladium metal olefin, and the commercial palladium / carbon catalyst;
[0031] Figure 12 Comparison of the catalytic activities of the edge-selectively etched palladium metal olefin-2 catalyst prepared in Comparative Example 2, the unetched palladium metal olefin, and the commercial palladium / carbon catalyst in 0.5 M H2SO4 + 0.5 M HCOOH solution;
[0032] Figure 13 These are scanning electron microscope images comparing the edges of palladium metal olefins before and after selective etching in Example 1. Detailed Implementation
[0033] To further illustrate the method and effects of the present invention, the following embodiments are provided for further explanation. Unless otherwise specified, specific conditions are generally applied according to conventional conditions or conditions recommended by the reagent company. Unless otherwise stated, all reagents and consumables used in the following embodiments are commercially available.
[0034] Example 1
[0035] The preparation method of the edge-selective etching palladium metal olefin catalyst in this embodiment includes the following steps:
[0036] (1) Add 40 mg of ammonium chloropalladate to 100 mL of methanol and mix evenly by ultrasonication at 60 °C. Then, introduce carbon monoxide and react for 15 minutes. After centrifugation and washing, palladium metal olefin is obtained.
[0037] (2) 10 mg of the prepared palladium metal olefin was ultrasonically dispersed in 30 mL of acetic acid solution with a concentration of 0.5 mol / L;
[0038] (3) Heat the solution after ultrasonic mixing in step (2) to 100°C under sealed conditions and keep it warm for 6 hours;
[0039] (4) The product obtained in step (3) is centrifuged, washed, and dried at 60°C for 10 hours to obtain the edge-selectively etched palladium metalene.
[0040] Figure 1The image shows a transmission electron microscope (TEM) image of the edge-selectively etched palladium metalene prepared in Example 1. The ultrathin structure of the palladium metalene is clearly visible in the image, and obvious etching is observed at the edges.
[0041] Figure 2 This is a comparison of cyclic voltammetry curves in 0.5 M H₂SO₄ solution for the edge-selectively etched palladium metalloene catalyst, the unetched palladium metalloene catalyst, and the commercial palladium / carbon catalyst prepared in Example 1. The electrochemically active specific surface areas of the commercial palladium / carbon catalyst and the unetched palladium metalloene catalyst were found to be 44.1 and 105.3 m², respectively. 2 g -1 Pd The edge-selective etching palladium metal olefin catalyst prepared in Example 1 exhibits higher electrochemical activity and a higher specific surface area (117.2 m²). 2 g -1 Pd This indicates that the edge-selective etching palladium metal olefin catalyst prepared in Example 1 has more catalytic active sites.
[0042] Figure 3 The graph shows a comparison of the current densities of the edge-selectively etched palladium metalloene catalyst and the unetched palladium metalloene catalyst prepared in Example 1, as well as the commercial palladium / carbon catalyst, in 0.5 M H₂SO₄ + 0.5 M HCOOH solution. The peak current densities for the commercial palladium / carbon catalyst and the unetched palladium metalloene catalyst are 596.5 mA and 1578.1 mg, respectively. -1 Pd The edge-selective etching palladium metal olefin catalyst prepared in Example 1 exhibited a higher peak current density (1942.5 mA mg). -1 Pd This indicates that the edge-selective etching palladium metal olefin catalyst prepared in Example 1 has higher catalytic activity for formic acid oxidation.
[0043] The experimental data above show that the planar structure of the palladium metal ene in Example 1 maintains a high degree of planarity due to the strong adsorption of carbon monoxide molecules, which inhibits the etching of acetic acid molecules. At the edges of the palladium metal ene, where there is little or no adsorption of carbon monoxide molecules, a chemical reaction occurs with acetic acid molecules, resulting in significant etching. The edge-selective etching palladium metal ene catalyst prepared in Example 1 has more active sites for formic acid oxidation and higher catalytic activity, far exceeding that of commercial palladium / carbon catalysts, thus showing significant application potential in direct formic acid fuel cells and other energy storage / conversion fields.
[0044] Example 2
[0045] The preparation method of the edge-selective etching palladium metal olefin catalyst in this embodiment includes the following steps:
[0046] (1) Add 40 mg of ammonium chloropalladate to 100 mL of methanol and mix evenly by ultrasonication at 60 °C. Then, introduce carbon monoxide and react for 15 minutes. After centrifugation and washing, palladium metal olefin is obtained.
[0047] (2) 10 mg of the prepared palladium metal olefin was ultrasonically dispersed in 30 mL of acetic acid solution with a concentration of 0.8 mol / L;
[0048] (3) Heat the solution after ultrasonic mixing in step (2) to 100°C under sealed conditions and keep it warm for 6 hours;
[0049] (4) The product obtained in step (3) is centrifuged, washed, and dried at 60°C for 10 hours to obtain the edge-selectively etched palladium metalene.
[0050] Figure 4 The image shows a transmission electron microscope (TEM) image of the edge-selectively etched palladium metalene prepared in Example 2. The ultrathin structure of the palladium metalene is clearly visible in the image, and the edge etching is more obvious.
[0051] Figure 5 This is a comparison of cyclic voltammetry curves in 0.5 M H₂SO₄ solution for the edge-selectively etched palladium metalloene catalyst, the unetched palladium metalloene catalyst, and the commercial palladium / carbon catalyst prepared in Example 2. The electrochemically active specific surface areas of the commercial palladium / carbon catalyst and the unetched palladium metalloene catalyst were found to be 44.1 and 105.3 m², respectively. 2 g -1 Pd The edge-selective etching palladium metal olefin catalyst prepared in Example 2 exhibits higher electrochemical activity and a higher specific surface area (125.2 m²). 2 g -1 Pd This indicates that the edge-selective etching palladium metal olefin catalyst prepared in Example 1 has more catalytic active sites.
[0052] Figure 6 The graph shows a comparison of the current densities of the edge-selectively etched palladium metalloene catalyst and the unetched palladium metalloene catalyst prepared in Example 2, as well as the commercial palladium / carbon catalyst, in 0.5 M H₂SO₄ + 0.5 M HCOOH solution. The peak current densities for the commercial palladium / carbon catalyst and the unetched palladium metalloene catalyst are 596.5 mA and 1578.1 mg, respectively. -1 Pd The edge-selective etching palladium metal olefin catalyst prepared in Example 2 exhibited a higher peak current density (2241.2 mA mg). -1 Pd This indicates that the edge-selective etching palladium metal olefin catalyst prepared in Example 2 has higher catalytic activity for formic acid oxidation.
[0053] The experimental data above show that the planar structure of the palladium metal ene in Example 2 maintains a high degree of planarity due to the strong adsorption of carbon monoxide molecules, which inhibits the etching of acetic acid molecules. At the edges of the palladium metal ene, where there is little or no adsorption of carbon monoxide molecules, a chemical reaction occurs with acetic acid molecules, resulting in significant etching. It should be noted that compared to Example 1, the higher concentration of acetic acid in Example 2 exacerbates the edge etching, leading to more pronounced etching. The edge-selective etching palladium metal ene catalyst prepared in Example 2 possesses more active sites for formic acid oxidation and higher catalytic activity, far exceeding that of commercial palladium / carbon catalysts, thus showing significant application potential in direct formic acid fuel cells and other energy storage / conversion fields.
[0054] Comparative Example 1
[0055] The preparation method of the edge-selective etching palladium metal olefin catalyst-1 in this comparative example includes the following steps:
[0056] (1) Add 40 mg of ammonium chloropalladate to 100 mL of methanol and mix evenly by ultrasonication at 60 °C. Then, introduce carbon monoxide and react for 15 minutes. After centrifugation and washing, palladium metal olefin is obtained.
[0057] (2) 10 mg of the prepared palladium metal olefin was ultrasonically dispersed in 30 mL of acetic acid solution with a concentration of 0.5 mol / L;
[0058] (3) Heat the solution after ultrasonic mixing in step (2) to 100°C under sealed conditions and keep it warm for 12 hours;
[0059] (4) The product obtained in step (3) is centrifuged, washed, and dried at 60°C for 10 hours to obtain the edge-selective etched palladium metalene-1.
[0060] Figure 7 Transmission electron microscope (TEM) image of edge-selectively etched palladium metalene-1 prepared for Comparative Example 1; the ultrathin structure of palladium metalene can be clearly seen from the image, and the edges show excessively severe etching.
[0061] Figure 8 The cyclic voltammetry curves of the edge-selectively etched palladium metal olefin catalyst-1 and the unetched palladium metal olefin catalyst, as well as the commercial palladium / carbon catalyst, in 0.5 M H₂SO₄ solution are compared. The electrochemically active specific surface areas of the commercial palladium / carbon catalyst and the unetched palladium metal olefin catalyst were found to be 44.1 and 105.3 m², respectively. 2 g -1 Pd The edge-selective etching palladium metal olefin catalyst-1 prepared in Comparative Example 1 exhibited an electrochemically active specific surface area of 108.1 m². 2 g -1Pd This indicates that the edge-selectively etched palladium metal olefin catalyst-1 prepared in Comparative Example 1 has a similar number of catalytic active sites as the unetched palladium metal olefin catalyst.
[0062] Figure 9 The current density comparison graph for the edge-selectively etched palladium metal olefin catalyst-1, the unetched palladium metal olefin catalyst, and the commercial palladium / carbon catalyst prepared in Comparative Example 1 in 0.5 M H₂SO₄ + 0.5 M HCOOH solution is shown. The peak current densities for the commercial palladium / carbon catalyst and the unetched palladium metal olefin catalyst are 596.5 mA and 1578.1 mg, respectively. -1 Pd The edge-selective etching palladium metal olefin catalyst-1 prepared in Comparative Example 1 exhibited a peak current density of 1580.2 mA mg. -1 Pd This indicates that the edge-selectively etched palladium metal olefin catalyst-1 prepared in Comparative Example 1 exhibits significantly higher formic acid oxidation catalytic activity compared to commercial palladium / carbon catalysts. However, compared to unetched palladium metal olefin catalysts, both exhibit similar formic acid oxidation catalytic activities.
[0063] The experimental data above indicate that extending the heating time to 12 hours in Comparative Example 1 resulted in excessive etching of the palladium metal ene edge. This led to an electrochemically active specific surface area and formic acid oxidation peak current density similar to those of the unetched palladium metal ene catalyst in electrochemical tests. Furthermore, the edge-selectively etched palladium metal ene catalyst-1 prepared in Comparative Example 1 exhibited lower electrochemically active specific surface area and formic acid oxidation peak current density than the edge-selectively etched palladium metal ene catalysts prepared in Examples 1 and 2.
[0064] Comparative Example 2
[0065] The preparation method of this comparative example of edge-selective etching palladium metal olefin catalyst-2 includes the following steps:
[0066] (1) Add 40 mg of ammonium chloropalladate to 100 mL of methanol and mix evenly by ultrasonication at 60 °C. Then, introduce carbon monoxide and react for 15 minutes. After centrifugation and washing, palladium metal olefin is obtained.
[0067] (2) 10 mg of the prepared palladium metal olefin was ultrasonically dispersed in 30 mL of sulfuric acid solution with a concentration of 0.5 mol / L;
[0068] (3) Heat the solution after ultrasonic mixing in step (2) to 100°C under sealed conditions and keep it warm for 6 hours;
[0069] (4) The product obtained in step (3) is centrifuged, washed, and dried at 60°C for 10 hours to obtain the edge-selective etched palladium metalene-2.
[0070] Figure 10 Transmission electron microscope (TEM) image of edge-selectively etched palladium metalene-2 prepared for Comparative Example 2; it can be clearly seen from the image that although palladium metalene can maintain a certain lamellar structure, its surface undergoes severe deformation and obvious agglomeration.
[0071] Figure 11 The figure shows a comparison of the cyclic voltammetry curves of the edge-selectively etched palladium metal olefin catalyst-2 and the unetched palladium metal olefin catalyst prepared in Comparative Example 2, as well as the commercial palladium / carbon catalyst, in 0.5 M H₂SO₄ solution. The electrochemically active specific surface areas of the commercial palladium / carbon catalyst and the unetched palladium metal olefin catalyst were found to be 44.1 and 105.3 m², respectively. 2 g -1 Pd The edge-selective etching palladium metal olefin catalyst-2 prepared in Comparative Example 2 exhibited an electrochemically active specific surface area of 78.2 m². 2 g -1 Pd This indicates that although the edge-selectively etched palladium metal olefin catalyst-2 prepared in Comparative Example 2 exhibits more catalytic active sites than commercial palladium / carbon catalysts, it is far less than the number of catalytic active sites in the unetched palladium metal olefin catalyst.
[0072] Figure 12 The graph shows a comparison of the current densities of the edge-selectively etched palladium metal olefin catalyst-2 and the unetched palladium metal olefin catalyst, as well as the commercial palladium / carbon catalyst, in 0.5 M H₂SO₄ + 0.5 M HCOOH solution, as shown in Comparative Example 2. The peak current densities for the commercial palladium / carbon catalyst and the unetched palladium metal olefin catalyst were found to be 596.5 mA and 1578.1 mg, respectively. -1 Pd The edge-selective etching palladium metal olefin catalyst-2 prepared in Comparative Example 2 exhibited a peak current density of 1216.5 mA mg. -1 Pd This indicates that the edge-selectively etched palladium metal olefin catalyst-2 prepared in Comparative Example 2 has significantly higher formic acid oxidation catalytic activity compared to commercial palladium / carbon catalysts, but exhibits much lower formic acid oxidation catalytic activity than the unetched palladium metal olefin catalyst.
[0073] The experimental data above show that replacing the 0.5 mol / L acetic acid solution with a 0.5 mol / L sulfuric acid solution in Comparative Example 2 resulted in a significant change in the surface structure of the palladium metal ene—the lamellar structure shrank and agglomerated, leading to an electrochemically active specific surface area and formic acid oxidation peak current density that were similar to those of the unetched palladium metal ene catalyst. Furthermore, the edge-selectively etched palladium metal ene catalyst-2 prepared in Comparative Example 2 exhibited lower electrochemically active specific surface area and formic acid oxidation peak current density than the edge-selectively etched palladium metal ene catalysts prepared in Examples 1 and 2.
[0074] Figure 13 The images shown are scanning electron microscope comparison images of the palladium metal olefin edge before and after selective etching in Example 1, which further verify the effectiveness of the appropriate technical solution.
[0075] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and detail without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing palladium metal olefins by edge selective etching, characterized in that, Includes the following steps: (1) Dissolve the palladium precursor in methanol, pass carbon monoxide gas through it, react to generate palladium metal olefin, centrifuge and wash to obtain palladium metal olefin. (2) Disperse palladium metal olefin in acetic acid solution; (3) After sealing and heating the mixed solution obtained in step (2), keep it at a constant temperature; (4) The product obtained in step (3) is centrifuged, washed and dried to obtain the edge-selectively etched palladium metalene.
2. The method for preparing edge-selectively etched palladium metal olefin according to claim 1, characterized in that, Palladium precursors include ammonium chloropalladate, sodium chloropalladate, or potassium chloropalladate.
3. The method for preparing edge-selectively etched palladium metal olefin according to claim 2, characterized in that, The mass-to-volume ratio of palladium to methanol in the palladium precursor is 0.05–50:1 mg / mL.
4. The method for preparing edge-selectively etched palladium metal olefin according to claim 1, characterized in that, The concentration of the acetic acid solution is 0.1–1.0 mol / L.
5. The method for preparing edge-selectively etched palladium metal olefin according to claim 4, characterized in that, The mass-to-volume ratio of palladium metal olefin to acetic acid solution is 0.1–50:1 mg / mL.
6. The method for preparing edge-selectively etched palladium metal olefin according to claim 1, characterized in that, In step (3), the heating temperature is 80℃~110℃.
7. The method for preparing edge-selectively etched palladium metal olefin according to claim 6, characterized in that, The heat preservation time is 2.0h to 10h.
8. The method for preparing edge-selectively etched palladium metal olefin according to claim 1, characterized in that, The drying temperature is 40℃~100℃, and the time is 10~20h.
9. An application of an edge-selectively etched palladium metal olefin prepared by the method of claim 1, characterized in that, The edge-selectively etched palladium metal olefin is used directly as an anode catalyst for formic acid fuel cells.
10. The application of the edge-selective etching of palladium metal olefins according to claim 9, characterized in that, The edge-selective etched palladium metalene is also used as a catalyst in biosensing, industrial catalysis, or metal-air batteries.
